Rational surface functionalization on mesoporous silica nanoparticles for targeted and controlled drug delivery - Tan, Si Yu (2016)
Mesoprous silica nanoparticles (MSNPs) are commonly used in the area of drug delivery due to their high surface area, large volume and easy functionalisation. In our study, we aim to improve the design of these MSNPs for drug delivery application. Hence, Chapter 2 utilizes MSNPs that are conjugated with a neuronal cell targeting ligand and the results obtained showed positive uptake into neuronal cells. As the neuronal cell targeting ligand was also known to be expressed in some cancer cell lines, Chapter 3 focuses on the use of this ligand together with the use of anticancer drug, Doxorubicin (DOX), to study their simultaneous effect on B16F10 melanoma cancer cell line and NIH3T3 normal cell line. A synergistic effect was observed when both the ligand and Dox was used. Besides using targeting moieties on MSNPs, the drug loading and release mechanism of MSNPs was optimized with a catalysis screening method in Chapter 4. It was concluded that moderate chain length with intermediately bulky terminal group and low density of disulfide-appended functional ligands on the surface of MSNPs gave the best drug release profiles. In conclusion, the above methods have a common goal of improving the drug delivery efficiency of MSNPs.